Electrochemical copper dissolution: A benchmark for stable CO2 reduction on copper electrocatalysts - Speck, Florian; Cherevko, Serhiy (Electrochemistry Communications, 2020)
Copper is well known in fundamental electrocatalysis research due to its ability to selectively reduce CO2 to C2 products. Recent, more applied studies have revealed that electrolyzers based on Cu electrocatalysts can reach current densities of up to hundreds of mA cm−2. This opens up the opportunity for industrial application of Cu-based electrocatalysts. However, the stability of copper must first be assessed. In this communication we investigate the electrochemical corrosion behavior of copper in a broad pH window relevant to CO2 reduction applications. Using an electrochemical on-line inductively coupled plasma mass spectrometer (ICP-MS), we quantify Cu dissolution during anodic oxidation and during the reduction of electrochemically formed oxide species. We show that electrochemical oxidation of Cu leads to high dissolution in neutral and highly alkaline environments, while an intermediate pH of around 9–10 leads to minimal dissolution. The obtained results are discussed in relation to the CO2 reduction reaction to set a benchmark for stable Cu-based electrocatalysts.
CRIS-Team Scopus Importer:2020-05-12
Keywords: CO; Copper; Dissolution; ICP–MS; Stability